Penerapan Berbagai Bentuk Motivasi Dalam Peningkatan Prestasi Belajar Mahasiswa Di Universitas Pendidikan Indonesia - Mukhidin, Mukhidin (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2010)
Learning achievement is a main indicator to measure achievement in implementing curricula. It needs forms of motivation given by lecturers as an effort to foster students’ learning achievement in Universitas Pendidikan Indonesia. The question is what kind of learning motivation that should be used and how about achieving that. To explore that, the research was done in three faculties namely FPTK, FPOK, and FIP with the lecturers as research subject. Design and research method was done with descriptive method. The conclusion of this research shows that several forms of motivation given by lecture can enhance students’ learning achievement.